GRAPE SEED EXTRACT’S NEUROPROTECTIVE EFFECT AND PARKINSON’S DISEASE: A SYSTEMATIC REVIEW - Sharon Jessica Fandy (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Parkinson’s disease (PD) is the most common neurological disease globally, only second to Alzheimer’s disease. One of the emerging treatments for PD is nutraceuticals. Grape seed extract (GSE) has a high concentration of polyphenolic compounds possessing antioxidant and neuroprotective capacity that may be valuable for neurodegenerative diseases. So far, there is no review summarizing the neuroprotective effect of GSE on PD, even though it is crucial to provide an insight into GSE as a potential natural treatment for PD. This systematic review aims to summarize the neuroprotective effect of grape seed extract (GSE) in Parkinson’s Disease in vivo and in vitro and their mechanism. The author performed a literature search using PubMed, Science Direct, Scopus, Sinta, and Garuda databases with keywords comprising “Neuroprotective”, “Grape Seed,” and “Parkinson’s disease.” Out of 1611 studies retrieved, 20 articles fit the inclusion criteria and became the basis for this review. The author analyzed and extracted the records regarding the neuroprotective effect and potential anti-PD properties from the studies. The analysis summarized that GSE could significantly improve the biological hallmarks of PD with numerous mechanisms, including antioxidant, anti-inflammation, protection of dopaminergic neurons, anti-amyloid effect, anti-apoptotic, neurogenesis, and synaptogenesis. Although the precise mechanism underlying PD is still elusive, treatment should target not only a single cause of PD but instead several pathways that could lead to the disease. In conclusion, GSE should be considered a potential nutraceutical in clinical trials to prevent and alleviate Parkinson’s disease by multiple mechanisms.